Предмет: Алгебра,
автор: Artemka111111
Помогите пожалуйста!)
Представить в виде многочлена.
а)(b-5)(b-4)-3b(2b-3)
б)3x(x-2)-(x-3)²
в)5(a+1)²-10a
Ответы
Автор ответа:
0
b^2 - 9b + 20 - 6b^2 + 9b = - 5b^2 + 20
3x^2 - 6x - ( x^2 - 6x + 9) = 3x^2 - 6x - x^2 + 6x - 9 = 2x^2 - 9
5( a^2 + 2a + 1) - 10a = 5a^2 + 10a + 5 - 10a = 5a^2 + 5
3x^2 - 6x - ( x^2 - 6x + 9) = 3x^2 - 6x - x^2 + 6x - 9 = 2x^2 - 9
5( a^2 + 2a + 1) - 10a = 5a^2 + 10a + 5 - 10a = 5a^2 + 5
Автор ответа:
0
спасибо)
Автор ответа:
0
пожалуйста,успехов!)))
Похожие вопросы
Предмет: Биология,
автор: toppot1012
Предмет: Химия,
автор: lena3392
Предмет: История,
автор: isaevaizabella
Предмет: Биология,
автор: ОоI
Предмет: Математика,
автор: GIBADULLINANAT